Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan di Pabrik Gula Ngadiredjo Kediri - Riska Tsamrotul Umami (BIMA : Journal of Business and Innovation Management, 2020)
This research aims at analyzing the influence of working motivation and working environment toward employees’ performance in Sugar Factory of Ngadiredjo Kediri by using the research technique of quantitative data analysis and causal research method. The data was obtained from survey and questionnairs distributed to 159 employees of Sugar Factory of Ngadiredjo Kediri. This sample was taken from the population consisting of 256 employees by using random sampling, in which the sample is taken from the population randomly without considering their levels. The technique of data analysis used mulptiple linear regression. The results of hyphothesis testing showed that: (1) Working motivation partially and significantly influences employees’ performance in Sugar Factory of Ngadiredjo Kediri, (2) Working environment does not partially influence the employees’ performance but it significantly influences employees’ performance in Sugar Factory of Ngadiredjo Kediri, and (3) Working motivation and working environment simultaneously influence employees’ performance in Sugar Factory of Ngadiredjo Kediri.